Philippine medical thesaurus on anatomy musculoskeletal system - Hofileña, Joan Carlin Marie A.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2003)
The uncontrollable growth of information specifically in the field of Medicine, as a result of years of data acquisition raises a need for information management. Medicine, a distinct discipline due to the technicality and preciseness of terms, usually faces issues of vagueness and ambiguity in medical terms. The need for an effective tool to coordinate these terms and to promote efficiency in storage and information dissemination is highly acknowledged in this study.
Inspired by the UP College of Medicine - PGH, the study is deemed to create a Philippine Multilingual Thesaurus. With the aim of collecting index terms for the Musculoskeletal System, a component of the Philippine Medical Thesaurus, the study initiated the project by collecting terms from the MeSH.
Medical terms were translated to Tagalog terms with the use of dictionaries ranked by experts according to their comprehensiveness and authoritativeness. Interviews with medical and non-medical professionals were done to determine the validity of the translated terms in the field of medicine and in the society.
The thesaurus making was based on the ISO 5964, a standard guideline for multilingual thesaurus construction. Of the 175 terms on musculoskeletal system from MeSH, 61 were translated into Tagalog and were made as thesaurus entries; 18 had available definitions only and 68 terms neither had equivalent terms nor definitions. The study despite the hindrances and difficulties in gathering data, has a promise of a bright future for the organization of information in the field of medicine. With the recognition, and continuous support of information management, 10-15 years from now, the Multilingual Philippine Medical Thesaurus will be complete or almost complete.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Filipino -- Medicine; Subject headings, Filipino -- Anatomy; Subject headings, Filipino -- Musculoskeletal system; Filipino Language -- Medical Filipino